Design of a Website-Based Kos Management Information System with Waterfall Method - Fitri, Anindo Saka; ariq, Muhammad Akhtar; Viddyartha, Rayhan Nashrullah; Imroatunnadhiroh, Roudhotul Izzah (STMIK Banjarbaru, 2024)
In the digital era, the existence of a website is crucial for the boarding house industry services. However, a number of issues need to be addressed, such as design, functionality and effective communication. This research aims to develop an effective online platform to improve boarding house management services in the era of digitalization. Through the use of waterfall development methods, observations, and interviews, data was collected to design an integrated system. Use Case Diagrams describe user interactions, Class Diagrams show relationships between classes, and Activity Diagrams illustrate user activity processes. The results of website testing using the usability testing method from 23 users showed several deficiencies that needed to be corrected, but over all the results were satisfactory, with most users responding positively to the features provided. The developed online platform is able to increase efficiency and effectiveness in managing boarding houses in the era of digitalization, with various important contributions to the development of the industry.Keywords: Design; Website; Boarding house; WaterfallsÂ AbstrakDalam era digital, keberadaan website menjadi krusial bagi layanan industri indekos. Meskipun demikian, sejumlah masalah perlu diatasi, seperti desain, fungsionalitas, dan komunikasi efektif. Penelitian ini bertujuan untuk mengembangkan sebuah platform online efektif untuk meningkatkan layanan pengelolaan indekos di era digitalisasi. Melalui penggunaan metode pengembangan waterfall, observasi, dan wawancara, data dikumpulkan untuk merancang sistem terintegrasi. Diagram Use Case menggambarkan interaksi pengguna, Class Diagram menunjukkan relasi antar class, dan Activity Diagram mengilustrasikan proses aktivitas pengguna. Hasil dari pengujian website menggunakan metode usability testing dari 23 pengguna menunjukkan beberapa kekurangan yang perlu diperbaiki, namun secara keseluruhan mendapatkan hasil yang memuaskan, dengan kebanyakan pengguna merespons positif terhadap fitur-fitur yang disediakan. Platform online yang dikembangkan mampu meningkatkan efisiensi dan efektivitas dalam pengelolaan indekos di era digitalisasi, dengan berbagai kontribusi penting bagi perkembangan industri tersebut.Â Â